Early Sources of the Jaina Tradition - Bhat??t??a, Bam??si??dhara. Link
1 online resource
Keywords: Early Sources of the Jaina Tradition reconstructs the history of the early Jaina tradition through a close study of the available textual sources. It focuses on Prvantha, one of the 24 Jinas that are identified by the Jaina tradition as its main religious leaders of the current time cycle.It is a commonly accepted hypothesis of nineteenth-century scholarship that Prvantha, the 23rd Jina, is a historical figure whose teachings were slightly modified by Mahvra, the 24th Jina. The book challenges this hypothesis by analysing a wide range of textual sources, some of which have never been examined in the academic literature. The author shows that the teachings and narratives associated with Prvantha are the result of a construction related to a reform movement sometime after Mahvra. The work included a re-assessment of key terms and concepts of the early Jaina texts and Jaina chronology.Presenting an innovative analysis and a new interpretation of Jaina sources, this work is an invaluable contribution to studies of South Asian History and Religion.